Nanocommunication networks - Yupapin, Preecha P.; Mitatha, Somsak; Ali, Jalil; Teeka, Chat (My University, 2012)
Optical devices have become interesting tools that can be used in various applications. The use of such devices have been investigated in many areas such as E/O (electrical/optical) and O/E(optical/electrical) signal converters; optical signal processing; optical sensor; optical communication and medicine, etc. More interesting applications have been introduced such as the use of a micro/nano scale device, which has become both interesting and challenging. In this book, the behavior of light(light pulse) within the micro and nano scale device(ring resonator) is investigated. This can be integrated to form circuit and system devices that can be used for atom/molecule trapping and transportation; optical transistor; fast calculation device(optical gate); nanoscale communication and networks and a device for medical applications.